Quantum chemical study of p-toluenesulfonic acid, p-toluenesulfonate anion and the water-p-toluenesulfonic acid complex. Comparison with experimental spectroscopic data - Pejov, Ljupčo; Ristova, Mirjana; Soptrajanov, Bojan (Elsevier BV, 2011)
The 1:1 p-toluenesulfonic acid-water complex, p-toluenesulfonic acid itself and the p-toluenesulfonate anion were studied at HF and B3LYP/6-31+G(d,p) levels of theory. Full geometry optimizations of the aforementioned species reveal non-existence of ionic minima on the explored 1:1 p-toluenesulfonic acid-water complex potential-energy hypersurfaces (PEHSs), implying that two or three p-toluenesulfonate ions (+crystal field) are required to stabilize the ionic H(3)O(+)⋯C(6)H(4)(CH(3))SO(3)(-) species found in the crystal structure of p-toluenesulfonic acid monohydrate (in fact, oxonium p-toluenesulfonate). Harmonic vibrational analyses of the p-toluenesulfonic acid-water complex as well as of the p-toluenesulfonate anion were used to confirm some of our previous reassignments of bands in the vibrational spectra of p-toluenesulfonic acid monohydrate and several metal p-toluenesulfonates. According to the quantum chemical results, the symmetric SO(3) bending mode should appear at higher frequencies than the antisymmetric one. A more consistent interpretation of the region of appearance of the SO(3) stretching modes is proposed which is in excellent agreement with the experimental spectroscopic data. The frequency of the multireference benzenoid ν(14) (B(2u)) mode (the "Kekulé" type vibration) is excellently predicted at the B3LYP level of theory, while the HF methodology performs significantly poorer in this respect. The interaction energies as well as the vibrational frequency shifts of the most relevant modes are also presented for the 1:1 p-toluenesulfonic acid-water complex. The NBO analysis is employed to analyze the charge transfer interaction within the complex.